Flexible exchange rates and stabilization policy - Herin, Jan.; Lindbeck, Assar; Myhrman, Johan; Stockholm (London : Macmillan, 1977)
This volume tend to proffer solution to the problem created by the shift to greater exchange rate flexibility during the early 1970s. The papers presented at the conference highlights the need to strengthen the theory of flexible exchange rates and to improve its integration with macro theory and stabilization policy analysis.
Proceedings of a conference held in Stockholm, 1975, and organized by the Institute for International Economic Studies.
Originally published in The Scandinavian journal of economics, v. 78, no. 2, 1976.
Includes bibliographies.
usc 20/04/18
Loans
Keywords: Foreign exchange rates; Foreign exchange; International finance